Report on Delineation of Unit Areas of Insurance from Clustering Exercise in Bakool Region of Somalia for Implementation of Index-Based Livestock Insurance (IBLI) - Abdi, Abdisalam Mohamed; Dubad, Abdirahman Bare; Kone, Diba; Banerjee, Rupsha R.; Paliwal, Ambica; Whitbread, Anthony M. (International Livestock Research Institute, 2023)
The objective of this report is to conduct the participatory clustering exercise in Bakool through community participation for delineation of unit areas of insurance. Bakool is one of the of the regions of Somalia that is dominated by pastoralism and meets all the suitability criteria for IBLI implementation.